2020
DOI: 10.3389/fmed.2019.00333
|View full text |Cite
|
Sign up to set email alerts
|

Role of Complex Networks for Integrating Medical Images and Radiomic Features of Intracranial Ependymoma Patients in Response to Proton Radiotherapy

Abstract: Human cancers exhibit phenotypic diversity that medical imaging can precisely and non-invasively detect. Multiple factors underlying innovations and progresses in the medical imaging field exert diagnostic and therapeutic impacts. The emerging field of radiomics has shown unprecedented ability to use imaging information in guiding clinical decisions. To achieve clinical assessment that exploits radiomic knowledge sources, integration between diverse data types is required. A current gap is the accuracy with wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Recently, a study was performed in a network analysis framework, using imaging features extracted from magnetic resonance images in intracranial ependymoma, and showed that subnetworks clearly separated tumor and healthy tissues, and even reflected tissue heterogeneity inside the tumor. 29 However, to our knowledge, the present study is the first to exploit network analysis for identifying reproducible radiomic features.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, a study was performed in a network analysis framework, using imaging features extracted from magnetic resonance images in intracranial ependymoma, and showed that subnetworks clearly separated tumor and healthy tissues, and even reflected tissue heterogeneity inside the tumor. 29 However, to our knowledge, the present study is the first to exploit network analysis for identifying reproducible radiomic features.…”
Section: Discussionmentioning
confidence: 93%
“…At another end, new methods will emerge to provide better representations for the encoded inputs via concepts like networks deconvolution, inversion, and dissection, among others (see [ 95 ]). Fifth and last, in order to face the challenge of intratumor heterogeneity, the quantification of tumor abundance at the voxel level is becoming an important direction in response assessment and recurrence risk studies [ 4 , 95 , 96 , 97 ]. This might help the identification of subregions, for instance, those metabolically active and defined as high risk [ 92 ], and may also inspire strategy to mitigate the effects of unbalanced data (for instance, when an outcome is over-represented) and thus decisional bias [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the integration of high dimensional data, including imaging, genetic sequence, clinical data, and health records, introduces errors, approximations, and inaccuracies. Some solutions have been proposed, such as a complex network approach [ 70 ]. Finally, it is difficult to compare model performance among different studies for the lack of standards in algorithm implementation and data collection [ 71 ].…”
Section: Image Analytics and Radiomicsmentioning
confidence: 99%